API Based Reward Model to Improve Regularity and Efficiency in Management Institutes - Jhaveri, Chetan A. (Prabandhan: Indian Journal of Management, 2018)
Purpose: The purpose of this research study was to explore the application of reward practice in the academic institutes of India affiliated to UGC through mathematical model and the reward framework positively affecting institutional performance. Design/Methodology/Approach: A quantitative research approach was followed in this study. A mathematical model was developed using principle of polynomial interpolation and numerical analysis to design reward framework for the academic institutes. The validity and reliability of the model was assessed using different teaching credit workloads. Practical Implications: The research study contributed to human resource practices in academic institutes. Mathematical model for reward framework was developed in this study, which is positively related to improvement in organizational performance. Academic institutes may benefit from these results by implementing and emphasizing non-financial rewards as part of a total rewards package. Application of the model has potential to influence business school faculty members' work regularity patterns. Originality/Value : The study contributed to HR practices by shedding light on how to develop a reward framework using a mathematical model which can motivate employees to improve the efficiency in the academic institutes. Developed non-financial reward strategies can be a viable alternative to costly financial rewards to academic institutes that can lead to enhanced organizational performance in academic institutes.